Peningkatan Kompetensi Pengelasan Shielded Metal Arc Welding Bagi Masyarakat Desa Makarti Jaya Kabupaten Morowali - Kadriadi; Wirakusuma, Kadex Widhy; Hair, Jumaddil; Alfian, Muhammad; Fathurrasuli; Nugroho, Vincentius Sulistyo Aji; Yusdianto (Journal of Industrial Community Empowerment, 2023)
Mekarti Jaya Village is located in the PT Industrial Area. IMIP, the need for industrial workers in the PT area IMIP continues to increase as the investment value in the area increases. To prepare the people and youth of Mekarti Jaya village to be able to take advantage of job opportunities in industries located in the PT area. IMIP needs to carry out training to increase competency, especially in the field of Shielded Metal Arc Welding (SMAW) welding position 2F. The selection of SMAW welding training materials was based on survey results, in which the need for welding specialist workers was the greatest need for industries in the PT area. IMIP. Training activities are carried out for approximately 1 month, starting with the preparation, implementation, and training results stages. The activities were carried out on February 27–29, 2022. Training activities were carried out at the Morowali Metal Industry Polytechnic Machinery Maintenance Engineering study workshop. The training was attended by ± 16 young people and residents of the village of Mekarti Jaya. The results of the training carried out were an increase in understanding and knowledge before and after the training activities were carried out; this was shown by the results of the constant shape of the ridges, welding position 2F, and the results of the post-test.